ANALYSIS OF UTILIZATION CHLOROPHYLL-A CONCENTRATION DATA FROM REMOTE SENSING IMAGERY TO SUPPORT MARITIME SECURITY OPERATIONS (CASE STUDIES IN THE ARAFURA SEA) - Okol Sri Suharyo; Nawanto Budi Sukoco; Johar Setiadi; Eko Kurniawan (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
Indonesia is the largest archipelago in the world with a vast ocean area and the richness of the fish. It allows theoccurrence of crime at sea, for example, is a crime of theft of fish and other marine resources. Indonesia in theregard Indonesian Navy confronted with various obstacles, among others, the limitation of the number of patrolboats that are not proportional to the extent of waters that should be on the cover as well as the limitations ofthe available budget for operational activities in the framework of the implementation of law enforcementoperations related crime at sea. With the limitation of that than required effectiveness and efficiency inoperations to crime at sea can still be implemented and the richness of the sea remains awake.The utilization ofremote sensing satellite technology capable of delivering information quickly with a broad scope. This researchuse the MODIS Aqua Image data Level 2 to detect the distributions of chlorophyll-a concentration which is anindicator of the fertility of the waters of an area the area is closely connected with the fisheries through theimplementations process of bottom-up areas with transparent high fertility rate is an area that's prone to fishtheft crime occurred. From the result of the data processing MODIS-Aqua Satellite image pattern time andlocation of the concentration of chlorophyll-a and verified by VMS data indicate that there is a close relationshipwhere a times and areas with a high concentration of chlorophyll observed a lot of fishing activity, so it is used inthis research can be used as supporting data in determining the direction and timing of the operation inparticular operations against crimes the theft of fish, finally the marine security operations could become moreeffective and efficient and success can be further improved.Keywords: Sea area, chlorophyll-a, effective and efficient.